2021
DOI: 10.1016/j.anr.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a home-based exercise program among patients with lower limb spasticity post-stroke: A randomized controlled trial

Abstract: To evaluate the effectiveness of advanced practice nurseeguided home-based rehabilitation exercise program (HREPro) among patients with lower limb spasticity post-stroke. Methods: This randomized controlled study recruited 121 patients with lower limb spasticity poststroke. Intervention (n ¼ 59) and control (n ¼ 62) groups underwent 12-month HREPro and conventional rehabilitation, respectively, after discharge. The FugleMeyer assessment of spasticity measurement, modified Ashworth scale of motor function, 10-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Twenty-one randomised controlled trials compared home-based rehabilitation with institution-based rehabilitation on an inpatient or outpatient basis 23–43. Fifteen randomised controlled trials compared home-based rehabilitation with usual care, which was provided according to routine practice without the involvement of the research team and might include no therapy, home care, instructions for home rehabilitation, inpatient therapy and outpatient therapy 32 38 44–56. Five randomised controlled trials evaluated the effect of specific home-based interventions by comparing with blank control or sham control 57–61.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one randomised controlled trials compared home-based rehabilitation with institution-based rehabilitation on an inpatient or outpatient basis 23–43. Fifteen randomised controlled trials compared home-based rehabilitation with usual care, which was provided according to routine practice without the involvement of the research team and might include no therapy, home care, instructions for home rehabilitation, inpatient therapy and outpatient therapy 32 38 44–56. Five randomised controlled trials evaluated the effect of specific home-based interventions by comparing with blank control or sham control 57–61.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies did not describe the details of treatment strategy 28 29 32 33 37 43 48 50 52 56 68 70. Among 37 studies which reported the details of treatment strategy, 19 studies provided physical exercise practice,23 26 27 31 34–36 45–47 49 53 57–59 61 63 64 71 20 studies provided training of daily activities,23–27 30 36 38 45 46 53–55 58–61 65 66 71 8 studies provided task/functional-specific training35 39–42 51 61 69 and 2 studies provided constraint-induced movement treatment 44 62. Other treatments like speech and communication therapy,42 psychosocial intervention,67 emotion management,71 electromyography-triggered neuromuscular stimulation,26 27 environmental modification,47 64 application of leisure activities,66 67 71 providing adaptive aids and equipment,59 66 providing fall prevention strategies63 and providing splint or orthoses34 were also used as part of home-based interventions for patients who had a stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Studies (van Wijck et al, 2019;Wu et al, 2020) suggest that the need to attend a remote program is related to transportation issues (home-to-facility distance or access to reference rehabilitation centers). Although they have approved the remote program, they did not agree to stay on the remote mode when the face-to-face mode was available again (Chen et al, 2020).…”
Section: Programmentioning
confidence: 99%
“…Remote physical exercise programs (e.g., telerehabilitation, telemonitoring, or home-based rehabilitation) can offer guided exercises with remote monitoring to people with musculoskeletal and neurological disorders (Hosseiniravandi et al, 2020), who are isolated by social distance. Such remote monitoring allows health professionals to adapt the exercises and physical activities according to the needs of the individuals with neurological diseases (Laver et al, 2020), facilitates access to health services, and improves equity, thus reducing the costs of the rehabilitation programs (Chen et al, 2020;Ghorbel et al, 2020;Han et al, 2020;PUi Kei et al, 2020;Salawu et al, 2020;Zedda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic paralysis and motor control deficits contribute to significant limitations in physical and social functioning and impose a huge public health burden [ 5 ]. Exercise intervention is an integral part of the rehabilitation for motor impairments caused by stroke and has been shown to improve the walking function, balance control, and functional independence [ 6 8 ]. However, most exercise interventions, such as resistance-based exercises [ 6 ], body weight support treadmill training [ 9 ], virtual reality [ 10 ], and passive robots [ 11 ], require safety monitoring and are equipment-dependent.…”
Section: Introductionmentioning
confidence: 99%